Liquid‐Solid Combination Memristors with Switchable Resistance - Libing Duan; Xue Han; Ruochen Pei; Qianwen Peng; Shenghui Guo; Yangyang Li; Wangchang Geng (Advanced Electronic Materials)
Abstract Here a reconfigurable memristor is demonstrated by connecting ZnO film to a fluidic channel. The memristive characteristics are successfully demonstrated with an electrolyte solution. The benefit of using a microfluidic channel is that the memristive characteristics can be adjusted by changing the electrolyte solution in real‐time. The neuromorphic functions such as long‐term plasticity, Spiking‐Rate‐Dependent Plasticity (SRDP), and behavior associated with “learning experiences”are demostrated in the devices. The capability of real‐time manipulating of memristive characteristics enables diverse manipulations on memristive characteristics of the devices, by doping of different concentrated and type of ions in the ZnO film. The electrolyte solution will open new possibilities for resistance switch manipulations, for the next generation neuromorphic computing.